Blast resistance of externally prestressed RC Beam: A theoretical approach. (15th January 2019) - Fan, Yi; Chen, Li; Fang, Qin; Wang, Tengfei
Highlights: Combined elasto-viscoplastic rate-sensitive model with improved layered-section method. Predicted dynamic responses of EPC beams subjected to blast loads. Validated proposed approach by application to existing static and blast testing data. Discussed three parameters that significantly affect dynamic responses of EPC beams to explosion. Identified parameters that should be balanced to achieve higher blast resistance in design of EPC beams. Abstract: Externally prestressed reinforced concrete (EPC) is employed in long-span civil infrastructure, and a simplified dynamic analytical method is required to evaluate the blast-resistant performance of these EPC components. A theoretical approach is proposed that combines the elasto-viscoplastic rate-sensitive model with an improved layered-section method to predict the dynamic responses of EPC beams subjected to blast loadings, based on an equivalent single-degree-of-freedom system. A corresponding calculation program is compiled on the MATLAB platform. The proposed approach and the compiled program are validated by application to existing static and blast testing data, as well as the corresponding finite element calculation results. Three key parameters—the conventional reinforcement ratio ρ s, the prestressing reinforcement ratio ρ p, and the span-depth ratio l /h—that significantly affecting the dynamic responses of the EPC beam to explosion are discussed, providing useful design insights. The analytical results indicate that the determination of the three affecting parameters should be balanced to achieve a higher blast resistance in designing the EPC beam.